In-situ Sr isotopes for plagioclase from andesites from the Kueishantao island analysed by LA-MC-ICP-MS (S4) - Guo, Kun; Wang, Xiaoyuan; Chen, Shuai (In: Guo, K et al. (2021): In situ elemental, Sr isotope composition of plagioclase and elemental composition of clinopyroxene and thermobarometric data of andesite from Kueishantao, north of Taiwan, China [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.929297, 2021)
This dataset reports Sr isotopic ratios of plagioclase of andesite from Kueishantao, north of Taiwan, China. Sr isotope ratios of Pl were measured by a Neptune Plus MC-ICP-MS (Thermo Fisher Scientific, Bremen, Germany) in combination with a GeoLas HD excimer ArF laser ablation system (Coherent, Göttingen, Germany) at the Wuhan Sample Solution Analytical Technology Co., Ltd.
Keywords: andesite; clinopyroxene; in-situ mineral geochemistry; in-situ Sr isotope; plagioclase